Excavatability properties of rock masses having different weathering degrees: An example of Gümüşhane granitoid, Gümüşhane, NE Turkey - Alemda?, Selçuk; Kaya, Ayberk; Gürocak, Zülfü; Da?, Serhat (TMMOB - Jeoloji Muhendisleri Odasi, 2011)
The studies to determine the excavatability properties of rocks contribute to the applicability of the engineering project in terms of the cost of excavation. In this study, excavatability properties of Early Carboniferous aged Gümüşhane Granotiod outcropped in the residential area of Gümüşhane were examined. Firstly, four different areas were selected and the rock masses were grouped according to their degree of weathering based on the description criteria of ISRM. As a result of these studies, the rock masses in field-1, field-2 and field-3 were determined as moderately weathered. The weathering degree of rock mass in field-4 was highly weathered. In the second stage, properties of discontinuities and geomechanical parameters of intact rock material were determined. In the next stage, RMR89, Q and GSI values of rock masses were determined and the rock masses were classified using the excavatability classification systems. Moderately and highly weathered rock masses were classified to be in ripping and digging categories, respectively. It was determined that the moderately weathered rock masses were ripped by using hydraulic breaker and the highly weathered rock masses were digged by using face shovel. In the final stage, the data obtained from these studies and the excavation works in the selected areas were compared. According to the results, the excavation methods suggested by Tsiambaos and Saroglou (2009) are completely compatible with in-situ excavation works.
Farklı Ayrışma Derecesine Sahip Kaya Kütlelerinin Kazılabilirlik Özellikleri: Gümüşhane Granitoyidi Örne?i, Gümüşhane, KD Türkiye
Keywords: Degree of weathering; Excavatability classification systems; Gümüşhane granitoid